Making appropriate speech act of apology in target language.: Making appropriate speech act of apology in target language. - Majidova, Gulruh (Maktabgacha taʼlim jurnali, 2022)
Abstract: The article deals with how to make the speech act of apology appropriately in international setting. The situations in which one has to apologize from someone else occur unintentionally quite often. So it is essential for language learners to be aware of the strategies of apologizing to avoid from face threatening act whenever they are guilty for something. The article informs the ways, strategies and helpful expressions which should be employed in saying sorry accompanied with some exercises that help the learners to consolidate what they have learnt.